Gorontalo City People's Opinion On 2023 Legislative Candidates - Elin H. Danial; Ikram Muhammad; Frezy Paputungan (Governance: Jurnal Ilmu Administrasi Publik, 2023)
Bawalsu Gorontalo City Supervises the Submission of the Results of Administrative Verification of Documents for Candidates for the 2024 Gorontalo City DPRD. Chairman of the Gorontalo City Bawalsu Alvian Mato when receiving the minutes of the results of the administrative verification of documents for candidates for the Gorontalo City DPRD for the 2024 election, Saturday (24/06/2023) Bawalsu Gorontalo City (24/06/2023) attended and supervised the submission of the results of administrative verification of documents for candidates for the 2024 Gorontalo City DPRD election. The activity which was held at the KPU Hall of Gorontalo City was attended by the chairman of the Gorontalo City Bawalsu Alvian Mato and members of the Gorontalo City Bawalsu Lukman A. Rahman and Hi. Fatahilla. Chairman and members Bawalsu Gorontalo City Supervises the Submission of the Results of Administrative Verification of Documents for Candidates for the 2024 Gorontalo City DPRD. Chairman of the Gorontalo City Bawalsu Alvian Mato when receiving the minutes of the results of the administrative verification of documents for candidates for the Gorontalo City DPRD for the 2024 election, Saturday (24/06/2023) Bawalsu Gorontalo City (24/06/2023) attended and supervised the submission of the results of administrative verification of documents for candidates for the 2024 Gorontalo City DPRD election. The activity which was held at the KPU Hall of Gorontalo City was attended by the chairman of the Gorontalo City Bawalsu Alvian Mato and members of the Gorontalo City Bawalsu Lukman A. Rahman and Hi. Fatahilla. Chairman and members of the Gorontalo City KPU, Secretary of the Gorontalo City KPU and their staffs as well as from the chairman and LO of the pokitik party in Gorontalo City. In this activity, KPU chairman Sukrin Saleh Taib gave a speech as well as opened the event. Where in his speech said that the KPU.